How Albanian Private Universities can use Game Theory for Optimization of Scholarship Offers - Sota, Llambrini; Kolaneci, Fejzi (European Journal of Sustainable Development, 2013)
There are 46 private universities in Albania. We believe that the tuition fee andscholarship for high GPA students are two important components of the competitionbetween private universities. This study is a first attempt in applying Game Theory foroptimization of scholarship offers by Albanian private universities during academic years.There is a conflict between the utility functions of shareholders to maximize their profitsand the utility functions of the students enrolled in private universities to minimize theirexpenses. The best solution of the conflict is a Nash equilibrium or Bayes-Nash-Harsanyiequilibrium, respectively. We prove the existence of these equilibria. However, there existmany equilibria, depending of private information. We interpret the Boyes-Nash-Harsanyiequilibrium solution as the set of possible rational concessions made by all players.